Primeira ocorrência de ovo amniótico na formação romualdo (cretáceo inferior da bacia do Araripe, Simões-Pi). - Sousa, Antônia Dayanne Abreu de (2018)
Fossil amniotic eggs have great informative potential, especially with respect to reproductive and evolutionary aspects of vertebrates. However, there are only a few intact specimens, or those with fossilized embryos within, and the rare reported cases are essentially related to dinosaurs. In Brazil, the records of these ichnofossils are practically restricted in the Bauru Basin. This research aimed to analyze the morphostructural characteristics of the first amniotic egg found in the carbonate concretions of the Romualdo Formation (Lower Cretaceous from Araripe Basin), adding information both in the study of these fossils and in the paleontological context of the basin. The specimen was collected at the site Sítio Pé da Serra do Félix, in the municipality of Simões, Piauí, Brazil, and it is deposited in the fossil collection of the Dom José Museum, in Sobral, Ceará. The methodology employed was based on Scanning Electron Microscopy, Energy Dispersive Spectroscopy and Optical Microscopy techniques, as well as Computed Tomography. It was possible to observe and describe morphological and microstructural characteristics of the shell, and to ascribe the specimen to crocodiloid morphotype. The diameters of the specimen point it as the smallest Crocodylomorpha egg already described for the Cretaceous. The shell has a thickness considered thick, especially when compared to other fossilized eggs reported for Brazil. The tomographic sections revealed basic structures of an embryo inside the egg, suggesting that this is the first fossilized egg with Crocodylomorpha embryonic trace in the world.